Characterisation of a detector based on microchannel plates for electrons in the energy range 10-20 keV - Moldovan, G; Matheson, J; Derbyshire, G; Kirkland, A (2008)
As part of a feasibility study into the use of novel electron detectors for an X-ray photoelectron emission microscope (XPEEM), we have characterised a detector based on microchannel plates (MCPs), a phosphor screen and a CCD camera. For XPEEM, an imaging detector is required for electrons in the energy range 10-20 keV. This type of detector is a standard fitment on commercial instruments and we have studied its performance in some detail in order to provide a baseline against which to evaluate future detector technologies. We present detective quantum efficiency (DQE), noise power spectrum (NPS) and modulation transfer function (MTF) measurements of a commercial detector, in the energy range of interest, as a function of the detector bias voltage. © 2008 Elsevier B.V. All rights reserved.